2014
DOI: 10.1007/s10545-014-9728-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of enzyme replacement therapy in adults with late‐onset Pompe disease: results from the NCS‐LSD cohort study

Abstract: The results of this longitudinal cohort study of 62 adults with late-onset Pompe disease, provide further evidence on the effectiveness of ERT in this rare condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 30 publications
8
51
1
3
Order By: Relevance
“…An increase in respiratory rate during the CPET (data not shown) could allow the patients to increase their peak VO2 despite a worsening of respiratory muscles' function. These observations are in agreement with previous studies performed in large samples of patients, which showed that the effects of ERT are less evident on respiratory than on peripheral muscles [12,26,27].…”
Section: Discussionsupporting
confidence: 93%
“…An increase in respiratory rate during the CPET (data not shown) could allow the patients to increase their peak VO2 despite a worsening of respiratory muscles' function. These observations are in agreement with previous studies performed in large samples of patients, which showed that the effects of ERT are less evident on respiratory than on peripheral muscles [12,26,27].…”
Section: Discussionsupporting
confidence: 93%
“…*In (a) patient numbers represent the total number of patients included in the studies reporting results at group level for the respective outcome measures (see for details Table ), while in (b) only those who actually performed the respective tests are included. Individual responses were not reported for the 6‐MWT and (F)VC in studies and , and for strength not in , and .…”
Section: Resultsmentioning
confidence: 99%
“…Many of those studies followed up patients for 1 year [24], 3 years [17,18,42] and 4 years [19]. All publications pointed out the difficulties to obtain consistent outcome measures in LOPD patients due to heterogeneous presentation of the disease and natural course and the high variability of individual response.…”
Section: Discussionmentioning
confidence: 99%